Improving transitional care after acute myocardial infarction: A scoping review - Filipa Homem; Anaísa Reveles; António Amaral; Verónica Coutinho; Lino Gonçalves (Wiley, 2024)
Abstract Cardiovascular disease remains the leading cause of morbidity and mortality, posing a significant challenge to healthcare systems worldwide. Transitional care interventions, which ensure coordination and continuity of care as patients move between different levels of healthcare, have been shown to reduce unnecessary healthcare utilization and improve patient outcomes. While much attention has been given to transitional care in heart failure, this review aims to map the interventions implemented for patients following an acute myocardial infarction (AMI). A scoping review was conducted following the Joanna Briggs Institute (JBI) methodology, with literature searches performed in the Cochrane, CINAHL, MEDLINE, JBI, and SciELO databases, focusing on publications from 2013 onwards in both Portuguese and English. Seventy‐five studies were included, with most combining multiple interventions that contributed to improved cardiovascular health outcomes, including increased adherence to healthy lifestyle behaviors, enhanced medication compliance, and better healthcare self‐management. These interventions were effective in reducing cardiovascular‐related Emergency Department visits, unplanned 30‐day readmissions, and mortality following a first‐time myocardial infarction. Key strategies identified included discharge planning, digital health solutions, outpatient care, and healthcare coordination. The findings of this review underscore the need for developing methodologies that enhance the transition of care from hospital to primary care following an AMI. There is an urgent need to design and implement new healthcare programs that integrate discharge interventions, digital health, outpatient care, and healthcare coordination to ensure continuity of care and optimize patient outcomes post‐discharge.